Study of Serum Level of Interleukin 2, Interleukin 10 and Tumor necrosis factor-α in sample of Iraqi psoriasis patients (Journal of the College of Basic Education, 2022)
The aim of this study was to determine the Th1 and Th2 serum cytokines, in patients with psoriasis and to compare their cytokine levels with those of normal control subjects. where study included 55 Iraqi patients with psoriasis:30 (15 females ,15 males) were untreated with any drugs. The other patient group consist of 25 (9 female and 16 male) treated with a biological treatment (infliximab) ,and 30 healthy control group were withdrawn (5) ml of venous blood for both patients and members of the control ,to conduct Immunological tests to determine the quantitative for each of level of IL-2,IL-10 and TNF-α in a manner (ELISA). The results showed significant increase in the level of probability (P <0.05) in the rate of level of IL-10 and TNF-α in patients compared to the control (healthy) .As well as the result also show no significant increases of IL-2.From this we can deduce that pro inflammatory and anti-inflammatory cytokines have an important role in the pathogenesis of psoriasis, the increase of IL-10 and TNF-α indicated the balance between the proinflammatory and the anti-inflammatory cytokine